Impact of Fc N-glycan sialylation on IgG structure. Issue 8 (17th November 2019) - Zhang, Zhongqi; Shah, Bhavana; Richardson, Jason
ABSTRACT: Human IgG antibodies containing terminal alpha 2, 6-linked sialic acid on their Fc N-glycans have been shown to reduce antibody-dependent cell-mediated cytotoxicity and possess anti-inflammatory properties. Although terminal sialylation on complex N-glycans can happen via either an alpha 2, 3-linkage or an alpha 2, 6-linkage, sialic acids on human serum IgG Fc are almost exclusively alpha 2, 6-linked. Recombinant IgGs expressed in Chinese hamster ovary (CHO) cells, however, have sialic acids through alpha 2, 3-linkages because of the lack of the alpha 2, 6-sialyltransferase gene. The impact of different sialylation linkages to the structure of IgG has not been determined. In this work, we investigated the impact of different types of sialylation to the conformational stability of IgG through hydrogen/deuterium exchange (HDX) and limited proteolysis experiments. When human-derived and CHO-expressed IgG1 were analyzed by HDX, sialic acid-containing glycans were found to destabilize the CH2 domain in CHO-expressed IgG, but not human-derived IgG. When structural isomers of sialylated glycans were chromatographically resolved and identified in the limited proteolysis experiment, we found that only alpha 2, 3-linked sialic acid on the 6-arm (the major sialylated glycans in CHO-expressed IgG1) destabilizes the CH2 domain, presumably because of the steric effect that decreases the glycan-CH2 domain interaction. The alpha 2, 6-linked sialic acid on the 3-arm (the major sialylated glycan in human-derived IgG), and the alpha 2, 3-linked sialic acid on the 3-arm, do not have this destabilizing effect.